Influence of Tenebrio molitor L Supplementation on Egg Quality and Omega-3 Content - Titim Rahmawati; Asnath Maria Fuah; Hadi Susilo Arifin; Muhamad Syukur; Salundik Dohong (Jurnal Ilmu Ternak dan Veteriner, 2022)
Tenebrio molitor L is one of the alternative feed ingredients because it is rich in nutrients, namely protein, vitamins, minerals (calcium), energy, and fat. Tenebrio molitor L also contains 33.64±0.22% omega-3, so it is hoped that the eggs produced contain omega-3. In this study 300 Lohman Brown laying hens of 20-week-old were used. Completely randomized design (CRD) was applied in this study with 3 treatments and 10 replications, each replication contained 10 laying hens. Treatments were: P0= Feed containing 5% MBM, P1= Feed containing 2.5% MBM + 2.5% Tenebrio molitor L, and P2= Feed containing 5% Tenebrio molitor L. This research was conducted for 6 months. The variables observed were egg production, egg weight, egg shape index, shell weight, shell thickness, Haugh unit, yolk index, and omega-3. Treatment had no influence on egg physical quality but had a significant influence on egg weight. Treatment P0 prodeced the lowest egg weight that was 59.02±0.53 g. Treatment P2 had higher omega-3 contents than P0 and P1 that was 88±0.12 mg 100 g-1. It was concluded that Tenebrio molitor L could replace MBM up to 5% in laying hens feed, improve eggs quality, and omega-3 content in eggs.